Ojcowskie pouczenie mądrościowe w Księdze Przysłów (1,8-9) - Nawrot, Janusz (Wydział Teologiczny UAM, 2008)
Prov 1:8-9 is an admonition to listen to and receive as one’s own the instruction that follows from parental experience. Its value is compared to a magnificent wreath on one’s head and to jewellery which lend splendour and glory to their owner. Wisdom, similarly to material goods, is worth desiring. However, the author encourages his audience to direct one’s desire for possessions toward wisdom which will never deteriorate or lose its lustre.
Paternal Wisdom Instruction in the Book of Proverbs (1,8-9)
Keywords: proverbs; admonition; wisdom; obedience; life; father/son relation